Evolution of relativistic outer belt electrons during an extended quiescent period. Issue 12 (3rd December 2014) - Jaynes, A. N.; Li, X.; Schiller, Q. G.; Blum, L. W.; Tu, W.; Turner, D. L.; Ni, B.; Bortnik, J.; Baker, D. N.; Kanekal, S. G.; Blake, J. B.; Wygant, J.
Abstract To effectively study loss due to hiss‐driven precipitation of relativistic electrons in the outer radiation belt, it is useful to isolate this loss by studying a time of relatively quiet geomagnetic activity. We present a case of initial enhancement and slow, steady decay of 700 keV–2 MeV electron populations in the outer radiation belt during an extended quiescent period from ∼15 December 2012 to 13 January 2013. We incorporate particle measurements from a constellation of satellites, including the Colorado Student Space Weather Experiment (CSSWE) CubeSat, the Van Allen Probes twin spacecraft, and Time History of Events and Macroscale Interactions during Substorms (THEMIS), to understand the evolution of the electron populations across pitch angle and energy. Additional data from calculated phase space density, as well as hiss and chorus wave data from Van Allen Probes, help complete the picture of the slow precipitation loss of relativistic electrons during a quiet time. Electron loss to the atmosphere during this event is quantified through use of the Loss Index Method, utilizing CSSWE measurements at low Earth orbit. By comparing these results against equatorial Van Allen Probes electron flux data, we conclude the net precipitation loss of the outer radiation belt content to be greater than 92%, suggesting no significant acceleration during this period, and resulting in faster electron loss rates than have previously been reported.